Mathematics Representation Skill Seen from Self-Efficacy in AIR Learning with Corrective Feedback - Risdianti, Ana; Kartono, Kartono; Masrukan, Masrukan (Universitas Negeri Semarang, 2021)
This research aims to describe mathematics representation skill of students seen from self-efficacy on Auditory Intellectually Repetition (AIR) learning with corrective feedback of VIII graders. This mixed method research used sequential explanatory design. The subjects were categorized based on self-efficacy categories: high, moderate, and poor. The data was collected by mathematics representation skill test, self-efficacy questionnaire, and interview. The findings showed that students taught by AIR with corrective feedback passed the actual minimum passing grade and had various descriptions of mathematics representation skill based on self-efficacy. It was shown by 4 high level self-efficacy students. They consisted of 3 high mathematics skill students and one moderate level students. From 23 moderate self-efficacy level students, there were 3 with high mathematics representation skill, 19 moderate skill, and one with poor skil. From 3 students with poor self-efficacy, there was only 1 moderate student and 2 poor level student.